Prarancangan Pabrik Amil Asetat dari Amil Alkohol dan Asam Asetat dengan Kapasitas 60.000 Ton/Tahun - , ANNISA MULIAHATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The preliminary design of this Amyl Acetate plant is intended to review the feasibility of this plant construction. The Amyl Acetate plant is designed to fulfill 60.000 tons/year capacity and this plant will be operated continuously for 330 days/year. In order to gain the product as the designed capacity, 40.528,15 tons/year of amyl alcohol and ton/year of acetic acid is required as the main raw material. The amyl acetate is produced by esterification process and catalyzed by Amberlyst 15 ion exchange. The reaction takes place in a fixed bed reactor in atmospheric condition. Extractive distillation column and decanter are needed as purification unit to get the 98,7% purity of Amyl Acetate product. The Amyl Acetate plant is located in Semarang, Central Java and required 75.000 m2 area and employs 216 labors. The energy consumed includes electricity about 189,94 kW and 2.551 kg/hour of fuel oil. Moreover, the utility requires 33.321 kg/hour of make-up water and 200 m3/hour of instrument air. Fixed capital costs $ 23.878.125,04 and Rp 6.700.508.187,35, working capital costs $ 806.357,05 and Rp 424.948.209.869,01, total production costs $ 7.250.779,12 and Rp 1.426.497.162.417,07. Based on the economical feasibility studies, this plant is categorized as low risk chemical plant with 27,46% ROI (before taxes), 2,67 years POT (before taxes), 55,69% BEP, 35,79% SDP, and 30,6% DCFRR. From those point, we can say that the preliminary design of this Amyl Acetate plant is quiet appealing for further studies.